Analysis of income, expenditure, and welfare of durian farmer households in Kemiri Village based on NTRPR - Mochammad Wisnu Wachidan; Nuriah Yuliati; Dona Wahyuning Laily (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2026)
Kemiri Village relies on the plantation sector, especially durian, as its main commodity. The decline in durian farming income over the past two years has prompted farming households to seek additional sources of income through off-farm and non-farm businesses. This study aims to (1) analyze the income and expenditures of durian farming households and (2) analyze the welfare levels of durian farming households. A quantitative descriptive method with stratified random sampling was employed based on the number of durian trees taken from 50% of the population, resulting in a sample of 53 respondents. The data analysis used included income, expenditure, contribution, and the Net Top Replacement Price Ratio (NTRPR) analysis. The results showed that the annual income from durian farming was IDR 311, 926, 385. Household expenditures amounted to IDR 43, 431, 073 per year, including food and non-food items. The welfare level of durian farmers using NTRPR with a value of 5.5 indicates that NTRPR > 1 means that, on average, farmers are able to meet the needs of their households from their agricultural and non-agricultural businesses. The results of this study highlight the importance of strengthening durian agribusiness and diversifying income to maintain the sustainable welfare of farming households in Kemiri Village.